Plickers digital resource for evaluating high school students (Research, Society and Development, 2020)
The Plickers application is a tool that allows the application of rapid tests in the classroom, which could be used to complement or replace traditional assessment. The objective of the present study was to demonstrate how the Plickers application can be used in evaluations, as well as to report classroom experiences after using this tool. The Plickers application consists of a website and an application available for smartphones that are free and available in the English language. To perform the test, students must be provided with answer cards containing four answer alternatives in square format. The side of the square pointing upwards provides the option of the alternative chosen by the student to answer the question. At the time of the test, the teacher starts the application on the smartphone and reads the answers. After application, he can access the answer files and download them, with all the questions answered. In this way, the Plickers tool allows the teacher to carry out constant evaluations, allowing to measure the student's learning from class to class, with a reduced expense of paper. It is important to note whether the school offers the resources, such as the internet and a multimedia projector, to implement the tool.